Pengaruh Metode Farming Gardening Project Terhadap Kemampuan Mengenal Konsep Ukuran Dan Kemampuan Kerja Sama Anak - Mailinda Anis Zulaiha; Miftakhul Jannah; Nurul Khotimah (UNIB Press, 2024)
This study aims to explore the effectiveness of the Farming Gardening Project program in improving 5-6 years old children's understanding of agriculture and gardening activities. The research method used was a pre-test post-test experiment with a control group design. Respondents consisted of 60 children aged 5-6 years who were randomly divided into two groups, namely the intervention group who participated in the Farming Gardening Project program and the control group who did not receive the intervention. The instruments used included a knowledge test about agriculture before and after the intervention as well as a participatory behavior rating scale in gardening activities. The results showed a significant increase in children's understanding of basic agricultural concepts in the intervention group after attending the Farming Gardening Project program, compared to the control group. In addition, children's active participation in gardening activities also increased significantly in the intervention group. Statistical analysis using independent t-test showed significant differences between the two groups (p < 0.05) in terms of children's knowledge and participation. The Farming Gardening Project program is effective in increasing 5-6 years old children's understanding of agriculture and promoting active participation in gardening activities. The implications of this study suggest the importance of integrating experiential learning approaches to enrich children's learning experiences in the context of agriculture and gardening activities.